A global Cndp1-knock-out selectively increases renal carnosine and anserine concentrations in an age- and gender-specific manner in mice - Weigand, Tim; Colbatzky, Florian; Pfeffer, Tilman; Garbade, Sven; Klingbeil, Kristina; Becker, Michael; Zemva, Johanna; Bulkescher, Ruben; Schürfeld, Robin; Thiel, Christian; Volk, Nadine; Reuss, David; et al. (International journal of molecular sciences, 2020)
Carnosinase 1 (CN1) is encoded by the Cndp1 gene and degrades carnosine and anserine, two natural histidine-containing dipeptides. In vitro and in vivo studies suggest carnosine- and anserine-mediated protection against long-term sequelae of reactive metabolites accumulating, e.g., in diabetes mellitus. We have characterized the metabolic impact of CN1 in 11- and 55-week-old Cndp1-knockout (Cndp1-KO) mice and litter-matched wildtypes (WT). In Cndp1-KO mice, renal carnosine and anserine concentrations were gender-specifically increased 2- to 9-fold, respectively in the kidney and both most abundant in the renal cortex, but remained unchanged in all other organs and in serum. Renal oxidized/reduced glutathione concentrations, renal morphology and function were unaltered. In Cndp1-KO mice at week 11, renal asparagine, serine and glutamine levels and at week 55, renal arginine concentration were reduced. Renal heat-shock-protein 70 (Hspa1a/b) mRNA declined with age in WT but not in Cndp1-KO mice, transcription factor heat-shock-factor 1 was higher in 55-week-old KO mice. Fasting blood glucose concentrations decreased with age in WT mice, but were unchanged in Cndp1-KO mice. Blood glucose response to intraperitoneal insulin was gender- but not genotype-dependent, the response to intraperitoneal glucose injection was similar in all groups. A global Cndp1-KO selectively, age- and gender-specifically, increases renal carnosine and anserine concentrations, alters renal amino acid- and HSP70 profile and modifies systemic glucose homeostasis. Increase of the natural occurring carnosine and anserine levels in the kidney by modulation of CN1 represents a promising therapeutic approach to mitigate or prevent chronic kidney diseases such as diabetic nephropathy.